2020
DOI: 10.1002/cncy.22314
|View full text |Cite
|
Sign up to set email alerts
|

Immediate histologic correlation in women with atypical squamous cells of undetermined significance cytology and positive high‐risk HPV: A retrospective review of 6000 cases in a large academic women's hospital

Abstract: Background Previous studies of the histologic correlation in women who have atypical squamous cells of undetermined significance cytology (ASC‐US) and are positive for high‐risk human papillomavirus (hrHPV+) have predominantly utilized the Hybrid Capture 2 (HC2) test, whereas the use of other US Food and Drug Administration (FDA)‐approved methods is relatively limited. Methods Cases of ASC‐US/hrHPV+ that were tested using HC2, Cervista, or Aptima were retrieved, and the immediate histologic correlations were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
1
10
1
Order By: Relevance
“…We understand that there are some serious limitations in this study. Although the prevalence of abnormal findings in this study seemed to be reasonable compared with those in some previous studies, 10 the sample size of this study may be small. Moreover, in this retrospective study, we cannot verify the presence of diagnosis difference or reliability among physicians.…”
Section: Discussioncontrasting
confidence: 42%
“…We understand that there are some serious limitations in this study. Although the prevalence of abnormal findings in this study seemed to be reasonable compared with those in some previous studies, 10 the sample size of this study may be small. Moreover, in this retrospective study, we cannot verify the presence of diagnosis difference or reliability among physicians.…”
Section: Discussioncontrasting
confidence: 42%
“…In addition, HPV-16 and 18/45 accounted for 47.1% of all CIN2+, and 79.8% of all SCC with HPV-16 alone accounting for 69.8% of all SCC. Thus, we are providing further evidence that persistent hrHPV infection is the primary cause of high-grade cervical disease, and persistent infection with HPV-16 and 18/45 pose higher risk for CIN2+ and SCC compared to other high-risk genotypes 31 , 35 - 37 . Our findings are consistent with those findings in the POBASCAN and ATHENA trials 25 , 26 , both of which demonstrated higher risk for precancer and cancer in HPV-16/18+ women than women positive for other high-risk genotypes.…”
Section: Discussionmentioning
confidence: 64%
“…A pooled hrHPV assay has been routinely used worldwide to stratify risks in women with ASC-US 31 . The ATHENA study demonstrated that HPV genotyping may be a promising risk stratification tool in aiding management decision-making for women with ASC-US 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, suspected glandular epithelial lesions are commonly diagnosed as atypical glandular cells (AGC), and they rarely occur in cases diagnosed as ASC‐US. The adenocarcinoma ratio among women with ASC‐US cytology is 0.18% and 0.1% according to statistics from our center and an American medical center, respectively 17,35 . Therefore, only squamous cells were used in training our model because training data contained annotated cells from cases diagnosed as LSIL, HSIL, and SCC.…”
Section: Discussionmentioning
confidence: 99%